Development of the Blended Learning AMIR Model Based on the Edu Virtual Laboratory History - Amirullah, Amirullah; Manda, Darman; A Kamaruddin, Syamsu (Ceddi Journal of Education, 2025)
This study aims to develop and validate the Blended Learning AMIR (Augmentation, Modification, Interactive, and Reflection) model for history education. The AMIR model represents an innovative integration of key elements from various established learning models, reconstructed to address the pedagogical demands of 21st-century learners. A distinctive feature of this model is its foundation in digital pedagogy, specifically through the utilization of the Edu Virtual Laboratory for History, which facilitates interactive and immersive learning experiences. The validation process yielded an average score of 3.69, indicating that the BL-AMIR model is considered valid by expert reviewers across all core components. These components include (1) syntax, (2) social system, (3) principles of reaction, (4) support system, and (5) instructional and nurturant effects, which collectively define the model’s structure and expected learning outcomes. The findings reveal that the BL-AMIR model enhances student engagement with authentic historical content, promotes problem-focused learning, and encourages meaningful collaboration. Furthermore, students demonstrated increased awareness of the benefits of combining online and face-to-face learning environments. The study concludes that the BL-AMIR model offers a significant pedagogical innovation for enhancing historical thinking and collaborative learning in blended educational settings.